Rancang Bangun Pengolahan Zakat, Infak, dan Sedekah - Arif Andi Susanto; Aristoteles Aristoteles; Machudor Yusman M (Jurusan Ilmu Komputer Fakultas MIPA Universitas Lampung, 2016)
Zakat, infak, and sedekah management was regulated in the Law of the Republic of Indonesia Number 23 of 2011 includes planning, collection, distribution, and utilization. They should also be managed institutionally with accordance of Islamic Shari'a, trusting, benefiting, justice, rule of law, integrated, and accountability. One objective of the Lembaga Amil Zakat (LAZ) is to colect and manage deposited of zakat, infak, and sedekah (ZIS) from muzakki to be distributed and utilized to mustahik accordance with Islamic Shari'a. Using and developing of System Information for ZIS is necessary, so zakat management on LAZ can be managed by an accountable and transparent. With ZIS System Information, it can be easier for officers in zakat data processing, provide the public in general and muzakki in particular to look directly existing information, and speed up the process of presenting information regarding the collecting and utilization of ZIS.Keywords: collection, infak, management, sedekah, utilization, zakat.